(untitled) (Hoboken, N.J., 2006)
Topics in Stereochemistry, previously edited by "the father of stereochemistry" Ernest L. Eliel, is a longstanding, successful series covering the most important advances in the field. The much-anticipated Volume 25 includes chapters on the following topics: Stereochemistry of molecules in inclusion crystals; Torsional motion of stilbene-type molecules in crystals; Supramolecular networks of porphyrins; Homo- and heterochirality in crystals; Supramolecular synthesis of 1D chains and 2D layers in hydrogen bond networks of ureas and 2-D pyrimidinones; Chiral auxiliaries powerful for both enantioresolution and determination of absolutely stereochemistry by X-Ray crystallograph; Engineering stereospecific reactoins in crystals: Synthesis of compounds with adjacent stereogenic quaternary centers by photodecarbonylation of crystalline ketones.
Keywords: Stereochemistry,Chemistry, physical